PENGARUH SARANA PRASARANA TERHADAP KUALITAS PEMBELAJARAN DI PAUD NAMRAJA DESA PERSIAPAN DERLALE - Aslin Trivena Manakutty; Livia A Tasidjawa; Hesty Matital; Jennifer Kapriati Titi; Diana Demitia Asomate (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to describe and analyze the influence of facilities and infrastructure on the quality of learning at PAUD Namraja, Derlale Preparation Village, Fena Leisela District, Buru Regency, Maluku. The study employed a descriptive qualitative approach with data collection through direct observation, in-depth interviews, and documentation review. Research informants consisted of the school principal and two classroom teachers. Results indicate that limitations in facilities and infrastructure including insufficient educational play equipment (APE), inadequate outdoor play facilities, and limited learning media significantly affect the quality of early childhood learning. Nevertheless, institutional self-reliance strategies through the use of local natural materials, community-based cooperative mechanisms, and synergy with the village government have proven capable of minimizing these limitations. Annual budget-based facility planning, though on a modest scale, demonstrates the accountability management supporting institutional sustainability.